A natural compound induced cardiogenic differentiation of endogenous MSCs for repair of infarcted heart - Lin, Xiaoli; Peng, Peng; Cheng, Lei; Chen, Shihui; Li, Karen; Li, Zhong Yu; Mo, Ye Hua; Zhou, Zhen; Li, Ming (Differentiation (London), 2012)
An intra-myocardial injection of a cardiogenic factor (cardiogenin) was reported to induce myocardial regeneration of exogenous mesenchymal stem cell (MSCs) origin. In this study, replacement of the dangerous intra-myocardial injection with a safe method and whether the endogenous MSCs contribute to the cardiogenin-mediated myocardial regeneration were investigated. Bone marrow transplantation with labeled MSCs was performed in rats, which were subsequently subject to a permanent ligation of left anterior descending coronary artery one week after the transplantation. The rats were then treated with the cardiogenin through oral administration for 2 weeks. We not only demonstrated the substantial therapeutic effects of cardiogenin on myocardial infarction through an oral administration, but also provided direct evidences that the bone marrow derived endogenous MSCs are the major cellular source of the regenerating myocardium. Preliminary mechanistic studies suggested that miR-9 and its target E-cadherin may be required for intercalated disc formation. ► A safe application of cardiogenin in heart infarction animal model was tested. ► Endogenous cellular origin of the regenerating myocytes was studied. ► Therapeutic effect of cardiogenin on MI by oral administration was demonstrated. ► Bone marrow derived MSCs are the major cellular source of the regenerating myocytes. ► E-cadherin and miR-9 may be required for cardiogenin-induced myocyte regeneration.